Cuidado de saúde do idoso, no domicílio: implicações para as cuidadoras, no distrito Ressaca - município de Contagem/MG - Hosana Ferreira Rates (2007)
This work is about the implications of elderly health care at domicile, for the caregivers, in the city of Contagem, Minas Gerais, Brazil. With the increase of life expectations and the prevalence of chronic-degenerative diseases, facing the humanization and de-hospitalization politics, the need to replace the model of attention is verified. It is essential to implement differentiated assistance actions, at domicile, as a privileged space to health care, in the direction of taking care of the growing demand of attention of elderly with chronic-degenerative diseases, overcoming the rationalization logic. However, it is verified that neither the supplemental health system, nor the public services consider the cost of the relatives, when they take responsibility for domicile care. With this research, I try to contribute to the analysis of those costs. This study has a descriptive-exploratory character. It uses a quantitative and qualitative approach, instruments, and data analysis. The general goal was to analyze the implications of domicile health care, given to people over 60, for the caregivers. The specifics goals were to know the relations that exist among the execution of domicile health care, to identify both emotional and financial costs of the caregivers with domicile health care, given to people over 60. The scenery chosen for this study was Ressaca district, because it is, in the city of Contagem, the district with the biggest number of people that are taken care of at home, in the area of the Family Health Program. The participants were 17 caregivers of elderly that depend of someone for daily life activities. The data collection period was from July third of 2006 to October second of 2006. The instruments uses to collect data were: domicile interview with the main caregivers, caregivers diary, field diary of the researcher and the charts with the records of the familys expenses with domicile care. The interviews were analyzed through exhaustive reading of the speeches from which were extracted the main ideas that were grouped in the construction of four empiric categories: The person taken care of; Caregivers: giving, learning and constructing; Care: construction and deconstruction and Care and expenses expression for the family. From those categories were included the data from the charts, from the care takers diary and the data analysis was made. When analyzing the data I could observe that the relations between the caregivers and the person being taken care of interact and have as interception the care that is influenced by the dedication of the caregivers, that are, mostly, women and relatives. I noticed that there are aspects in the relation caregiver/ person being taken care of that facilitate or make difficult the execution of home care. Humanizing attitudes were observed in the domicile locus. The caregivers dedication to the person-taken-care-ofs tasks directly influences quality of life, with loss of work opportunities, of social conviviality and leisure time, with repercussions in both physical and emotional health. The data reveal that the family doesnt account the expenses with the people that are domicile taken care of. It was necessary to appeal to price consultancy and relate them to the notes in the charts in order to come to an approximate value of the expenses with food, medication, consumption items, domicile internment services and instruments to the care execution. The consultations availability, the medication supply, the emergency service lab and hospital utilization, and the removals made by the Mobile Urgency Attendance System are items that help to reduce the budget expenses, representing financial economy to the relatives of the person being taken care of. However, this support is discontinued. The alimentation of the people taken care of is done according to the financial-economical-social situation and there are caregivers that report difficulty to buy food. The geriatric disposable diaper is the item of biggest impact on the family budget in the category of consumption items. If the payment of the domicile internment was made by the family, this would be the biggest expense, that could get as high as R$2,325.00. In second place would be health insurance (R$450.00) and, in third place, medications (R$376.55). In general, the caregivers live in a tight budget. The biggest support comes from the family that is fundamental for the domicile care, as the executer of the care and as the financer of the expenses that exceed the governmental benefits of the person being taken care of. In conclusion: although all the exercises recognized as essentials in the domicile care, this cannot be recognized as a substitutive model yet.